Strategic Enhancements for the Nixu Threat Intelligence Service - Näsman, Karin (My University, 2024)
Cyber threat intelligence refers to the process of gathering, analysing, and interpreting information related to cyber threats, vulnerabilities, and attack strategies to anticipate and mitigate potential security risks. In today’s interconnected world, where digital systems are deeply integrated into critical infrastructure, commerce, and daily life, the importance of threat intelligence has never been more pronounced. The current global landscape is marked by an increasing frequency of sophisticated cyber attacks from state-sponsored actors, organized crime, and independent hackers. These threats target not only financial gain but also seek to disrupt national security, destabilize economies, and erode public trust. This thesis explores strategic enhancements for Nixu Threat Intelligence (NTI) service, focusing on understanding customer values and identifying potential improvements. The primary objective was to ascertain what elements of the service customers appreciate and which areas could benefit from enhancements. To achieve this, a detailed survey was distributed to NTI customers, aiming to gather comprehensive insights into their engagement and satisfaction levels with different parts of the threat intelligence service. The survey results indicated a high level of customer engagement and satisfaction, with customers recognizing the service's value in their security operations. Customers provided a range of feedback, highlighting both strengths and areas for improvement. Key findings from the survey revealed that while the core features of the service are highly valued, there are specific enhancements that could further elevate the user experience and operational effectiveness. Based on these insights, the study proposes several strategic enhancements designed to align the service more closely with customer needs. These enhancements aim to provide more tailored and actionable intelligence, thereby increasing the overall utility and satisfaction of the service. Additionally, the study underscores the importance of maintaining a flexible and adaptive approach to service development, ensuring that the NTI service can continuously meet the evolving demands of its customers. The thesis concludes that threat intelligence as a service is crucial for customers' security strategies and will remain essential as cyber threats continue to evolve. This study contributes valuable insights into customer-centric service development and highlights the ongoing relevance and importance of threat intelligence in modern cyber security frameworks.
Keywords: threat intelligence, cyber security